2009
DOI: 10.1080/00288330909510033
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the time course of shade, temperature, and wood recovery in streams with riparian forest restoration

Abstract: action is increasingly being taken in New Zealand and elsewhere to restore ecological function to streams through planting of riparian zones. We used simulation modelling to explore the relative performance of three strategies to restore the riparian zone of a pastoral stream to native forest by: (1) passive regeneration; (2) planting then abandonment of a Pinus radiata plantation; and (3) active restoration by planting selected native trees. We linked the forest model liNkNZ with a shade and temperature model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Fallen timber, which provides habitat and food for many freshwater animals, may take a century to accumulate in streams following reforestation (Davies-Colley et al, 2009) and needs to be supplemented. Clearance of forests for agriculture generally increases sedimentation, clogging stream channels and crevices, which are used by many freshwater animals (Burcher et al, 2008).…”
Section: Diversity Of Freshwater Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fallen timber, which provides habitat and food for many freshwater animals, may take a century to accumulate in streams following reforestation (Davies-Colley et al, 2009) and needs to be supplemented. Clearance of forests for agriculture generally increases sedimentation, clogging stream channels and crevices, which are used by many freshwater animals (Burcher et al, 2008).…”
Section: Diversity Of Freshwater Animalsmentioning
confidence: 99%
“…Plant litter is an important structural component of forests and thick layers can accumulate within two decades when taxa such as Eucalyptus are planted . Reforestation may take >30 year to increase fallen timber on forest floors, which is a key resource for many taxa (Harmon et al, 1986), and centuries to attain levels in streams similar to those within mature forests (Davies-Colley et al, 2009).…”
Section: Development Of Forest Structurementioning
confidence: 99%
“…Buffer height generally is not considered, but DeWalle (2008a,b) and Davies‐Colley and Rutherford (2005) showed that buffer height and height to stream width ratios were major parameters controlling shading. Davies‐Colley et al. (2009) combined forest, stream shade, and stream temperature models to compare likely effects of different strategies for restoring riparian zones in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…McClurg, Petty, Mazik, & Clatyton, ). As pointed out by Davies‐Colley, Meleason, Hall, and Rutherford (), if the recovery of large trees providing wood to structure the channel is included, it may take centuries.…”
Section: Discussionmentioning
confidence: 99%